The use of promising entomopathogenic fungi for eco-friendly management of Helicoverpaarmigera Hubner in chickpea - Jamro, Hafeez-U-Rahman; Khaskheli, M. Ibrahim; Khaskheli, Allah Jurio; Jiskani, M. Mithal; Chang, Xiaoli; Gong, Guoshu; Poussio, Gul Bahar; Otho, Sohail Ahmed (International Journal of Environment, Agriculture and Biotechnology, 2019)
Gram pod borer, Helicoverpaarmigera Hubner is known to be a major constraint of chickpea production which causes serious economic loess. The management of this pest in any crop is always been challenge to the growers, famers and researcher. Thus, present study evaluated some promising entomopathogenic fungi for the sustainable management of H. armigera to minimize the economic loss in chickpea. Five different fungal isolates viz; Beauveriabassiana, Trichodermavirens, Trichodermahamatum, Trichodermakoningii, and Paecilomyces sp. were used as entomopathogenic against gram pod borer, through dipping and poison food methods under laboratory conditions. The entomopathogenic potential of different fungal strains revealed significantly (P<0.05 = 0.0000) highest mortality with B. bassiana (46.67%) followed by T. koningi (23.33%), T. virens (11.11%) and T. hamatum(8.33%) through dipping method. In case of poison food method significantly highest mortality was recorded with T. koningi (20%) followed by B. bassiana (6.66%) after 24 h. The mortality with B. bassiana after 96 h was become higher (41.667%) compared with other strains. No mortality was recorded with Paecilomyces sp. and control (dipped in simple water) in both methods. It is obvious that microbial control agents are very effective and the promising entomopathogenic fungi of current study are hoped would be helpful for eco-friendly and alternative to chemical pesticides for sustainable management of H. armigera in chickpea.